PICES Press, Vol. 24, No. 2, Summer 2016 - North Pacific Marine Science Organization (PICES) (North Pacific Marine Science Organization (PICES), 2016)
The 2016 Inter-sessional Science Board meeting: A note from the Science Board Chairman (pp. 1-3); PICES at the 9th International Conference on Marine Bioinvasions (pp. 4-6); The ICES/PICES 6th International Zooplankton Production Symposium (pp. 7-12); PICES/ICES Workshop on “Use of zooplankton indicators to characterize state of pelagic ecosystems” (pp. 13-14); PICES/ICES Workshop on “ICES/PICES cooperative research initiative” (pp. 15-16); PICES/ICES Workshop on “Zooplankton as a potential harvestable resource” (pp. 17-17); PICES/ICES Workshop on “A hands-on introduction to time series analysis, visualization and inter-comparison of plankton survey data” (pp. 18-20); PICES/ICES Workshop on “Toward a taxonomically-comprehensive global reference database for DNA barcodes of marine zooplankton” (pp. 21-23); MSEAS 2016—Understanding marine socio-ecological systems (pp. 24-25); The Little Green Bucket’s 10,000 mile journey (pp. 26-27); A community needs assessment for coastal Guatemala (pp. 28-31); GlobalHAB – a new initiative in the HAB community (pp. 32-32); IMBER – Synthesis and the way forward (pp. 33-35); GLODAPv2: Data synthesis product published at CDIAC (pp. 36-37); PICES calendar of upcoming events (pp.38-38); Important dates (pp. 39-39); PEEC 2016 – A West Coast conference (pp. 43-45); The Blob is gone (pp. 46-47); The state of the western North Pacific during the 2015/2016 cold season (pp. 48-50); The Bering Sea: Current status and recent trends (pp. 51-54)